Poesy the Monster Slayer - Doctorow, Cory (First Second, imprint of Roaring Books Press, 2020)
Once her parents are off to bed, Poesy excitedly awaits the monsters that creep into her room. With the knowledge she's gained from her trusty Monster Book and a few of her favorite toys, Poesy easily fends off a werewolf, a vampire, and much more.